Tuan Rumah yang Ramah, Tamu yang Rapuh, dan Kaum Peziarah: Misi Gereja yang Hospitabel Bertitik Tolak dari Peristiwa Pentakosta (Kis. 2:1-13) - Rommi Matheos (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2023)
AbstractThe idea of a hospitable mission is examined in this essay according to Amos Yong. He contends that the Incarnation and Pentecost, two significant events, are examples of how God’s kindness is displayed (Acts 2). God welcomes and embraces creation through the event of the Incarnation, whereas God lends Godself to creation through the event of Pentecost. The Pentecostal event is where the church’s ministry of hospitality began. The early Church experienced the new and ongoing presence of Jesus, and the Holy Spirit was instrumental in giving believers certainty of this presence. The hospitable theology of the Church’s mission, whose starting point came from the event of Christ’s Creative Transformation, is reconstructed using John B. Cobb, Jr.’s concept of Christ as Creative Transformation as a lens. AbstrakArtikel ini mengkaji konsep misi yang ramah menurut pendapat Amos Yong. Ia berpendapat bahwa hospitalitas Allah diwujudkan dalam dua peristiwa penting yaitu peristiwa Inkarnasi dan Pentakosta (Kis. 2). Melalui peristiwa Inkarnasi Allah menyambut/merengkuh ciptaan, sedangkan melalui peristiwa Pentakosta Allah memberikan diri-Nya kepada ciptaan. Misi Gereja yang ramah memiliki titik permulaannya pada peristiwa Pentakosta. Roh Kudus berfungsi untuk memberikan kepastian akan kehadiran Yesus secara baru dan terus menerus yang mewujud dalam kehidupan Gereja mula-mula. Konsep Kristus sebagai transformasi kreatif (Christ as Creative Transformation) dari John B. Cobb, Jr digunakan sebagai lensa untuk merekonstruksi teologi misi Gereja yang ramah yang titik permulaannya bermuasal dari peristiwa Pentakosta.